Optimization Of V-Bending Of Aluminium Aa6061 Strip Of Non-Uniform Profile Using The Taguchi Method - Adnan, Mohd Fitri (2017)
Automotive manufacturer are now producing ever lighter vehicles. Various techniques have been implemented to achieve this. Thickness variation is one of the effective approach in reducing weight. Formability of the non-uniform thickness section has been overlooked in the forming process of these parts. Improper process and incorrect decision may lead to severe defect and one of the main concerns is a springback. Springback is a common defect found in sheet metal forming which is mainly caused by the elastic recovery and redistribution of internal stress during unloading process. The effect of springback is to change the shape and dimension of the parts and can create major problem in the assembly. In this study, thickness ratio and stroke are two main parameters, followed by annealing temperature, rolling direction and alignment. Optimal parameters obtained using Taguchi Method where an L18 (61 × 34) orthogonal array with three column and eighteen rows and one parameter with six level and the other four parameters with three levels. Two profiles of thickness variation have been studied, tapered and parabolic profiles. The results for the tapered profile revealed that most significant parameter is stroke which contribute 87.57% followed by thickness ratio (2.94%), rolling direction (1.89%), the alignment (0.68%) and annealing temperature (0.42%), and while the result for curved shape showed that the most significant parameter is lead by stroke with 82.41% contribution followed by thickness ratio (2.60%), annealing temperature (2.30%), alignment (0.59%) and rolling direction (0.49%). Based on the result, it can be concluded that bend angle and thickness ratio are the most significant parameter that influence the springback behavior of the aluminium strip with non-uniform thickness section. The optimal combination of A3 B3 C3 D3 E2 for tapered shape and A2 B3 C3 D3 E3 for curved shape can result in minimum springback.